Crystal form of salt of JAK kinase inhibitor
By preparing and characterizing polymorphs of various salts of compound A, the problem of poor physical properties of compound A salts in pharmaceutical compositions was solved, achieving better physical stability and solubility, making it suitable for treating JAK kinase-mediated diseases.
Patent Information
- Application Number
- CN202411159185.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-23
- Filing Date
- 2024-08-22
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the salt of compound A lacks a crystal form suitable for reliable formulation and manufacturing, resulting in poor physical properties such as filterability, hygroscopicity, flowability and solubility, making it difficult to effectively apply to pharmaceutical compositions.
Polymorphs of different salts of compound A, including hydrochloride, sulfate, phosphate, fumarate, etc., were prepared. Their crystal forms were characterized by X-ray powder diffraction, differential scanning calorimetry and thermogravimetric analysis to ensure that they have specific X-ray powder diffraction patterns and thermal properties.
Compound A salts with multiple crystal forms are provided, which improve their physical stability and solubility in pharmaceutical compositions, making them suitable for treating JAK kinase-mediated diseases such as tumors and autoimmune diseases, and have better grinding, pressure stability and hygroscopicity.
Smart Images

Figure CN119504757A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to polymorphs of 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile salt and a preparation method thereof, as well as a pharmaceutical composition containing at least one polymorph and the therapeutic or preventive use of the polymorph and the composition. Background Art
[0002] 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile (Compound A) belongs to the JAK class of small molecule non-receptor tyrosine kinase inhibitors, and its JAK-STAT signaling pathway is closely related to inflammatory cytokines and tumors, and is widely involved in important biological processes such as cell proliferation, differentiation, metastasis, apoptosis, regulation of immune response and cell homeostasis in human health and disease. The art needs to further study the crystal form of the salt of Compound A, and needs to have a crystalline or amorphous form with physical properties suitable for reliable formulation and manufacturing, including filterability, hygroscopicity, fluidity, solubility, etc. Summary of the invention
[0003] The present application relates to crystalline forms of various salts of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile.
[0004] In the first aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile hydrochloride, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 5.2°±0.2°, 17.7°±0.2° and 10.4°±0.2°.
[0005] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 13.2°±0.2°, 26.4°±0.2°, and 19.9°±0.2°.
[0006] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 22.4°±0.2°, 28.6°±0.2°, and 26.0°±0.2°.
[0007] In one embodiment, the crystalline form has an X-ray powder diffraction pattern comprising peaks at diffraction angles 2θ of 5.2°±0.2°, 17.7°±0.2°, 10.4°±0.2°, 13.2°±0.2°, 26.4°±0.2°, 19.9°±0.2°, 22.4°±0.2°, 28.6°±0.2° and 26.0°±0.2°.
[0008] In one embodiment, the crystalline form has Figure 1 The X-ray powder diffraction pattern is shown.
[0009] In a second aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile hydrochloride, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 8.2°±0.2°, 9.9°±0.2° and 14.5°±0.2°.
[0010] In one embodiment, the X-ray powder diffraction pattern of the crystalline form also includes at least one peak located at a diffraction angle 2θ of 10.6°±0.2°, 11.0°±0.2°, 17.9°±0.2°, 19.1°±0.2°, 19.8°±0.2°, 20.3°±0.2°, 22.3°±0.2°, 25.3°±0.2° and 26.5°±0.2°.
[0011] In one embodiment, the crystalline form has Figure 5 The X-ray powder diffraction pattern is shown.
[0012] In the third aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile hydrochloride, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 10.7°±0.2°, 17.2°±0.2° and 24.5°±0.2°.
[0013] In one embodiment, the X-ray powder diffraction pattern of the crystalline form also includes at least one peak located at a diffraction angle 2θ of 7.4°±0.2°, 12.6°±0.2°, 15.7°±0.2°, 16.7°±0.2°, 20.2°±0.2°, 21.1°±0.2°, 26.7°±0.2°, 27.2°±0.2°, 28.8°±0.2° and 30.7°±0.2°.
[0014] In one embodiment, the crystalline form has Fig. 9 The X-ray powder diffraction pattern is shown.
[0015] In a fourth aspect, the present application relates to a crystalline form of compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile sulfate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 8.5±0.2°, 8.7°±0.2° and 12.5°±0.2°.
[0016] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 15.7±0.2°, 16.9°±0.2°, and 18.1°±0.2°.
[0017] In one embodiment, the crystalline form has Fig.13 The X-ray powder diffraction pattern is shown.
[0018] In a fifth aspect, the present application relates to a crystalline form of compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile sulfate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 3.4±0.2°, 14.8°±0.2° and 20.7°±0.2°.
[0019] In one embodiment, the X-ray powder diffraction pattern of the crystalline form also includes at least one peak located at a diffraction angle 2θ of 12.4±0.2°, 15.5°±0.2°, 16.9°±0.2°, 17.8°±0.2°, 20.4°±0.2°, 22.1°±0.2°, 24.9°±0.2°, 26.4°±0.2° and 27.8°±0.2°.
[0020] In one embodiment, the crystalline form has Fig.17 The X-ray powder diffraction pattern is shown.
[0021] In a sixth aspect, the present application relates to a crystalline form of compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile phosphate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 9.2±0.2°, 14.0°±0.2°, 17.0°±0.2° and 18.1°±0.2°.
[0022] In one embodiment, the X-ray powder diffraction pattern of the crystalline form also includes at least one peak located at a diffraction angle 2θ of 3.1°±0.2°, 6.8°±0.2°, 7.5°±0.2°, 12.5°±0.2°, 15.1°±0.2°, 16.5°±0.2°, 17.6°±0.2°, 17.9°±0.2°, 18.7°±0.2°, 19.0°±0.2°, 20.3°±0.2° and 21.6°±0.2°.
[0023] In one embodiment, the crystalline form has Fig.21 The X-ray powder diffraction pattern is shown.
[0024] In a sixth aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile fumarate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 7.2±0.2°, 41.7°±0.2° and 14.3°±0.2°.
[0025] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 13.5±0.2°, 22.3°±0.2°, 23.0°±0.2° and 25.3°±0.2°.
[0026] In one embodiment, the crystalline form has Fig.25 The X-ray powder diffraction pattern is shown.
[0027] In the seventh aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile fumarate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 8.6±0.2°, 9.8°±0.2° and 14.3°±0.2°.
[0028] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 7.2±0.2°, 11.7°±0.2°, 16.2°±0.2° and 26.9°±0.2°.
[0029] In one embodiment, the crystalline form has Fig.29 The X-ray powder diffraction pattern is shown.
[0030] In an eighth aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile fumarate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 9.2±0.2° and 14.2°±0.2°.
[0031] In one embodiment, the X-ray powder diffraction pattern of the crystalline form also includes at least one peak located at a diffraction angle 2θ of 7.1±0.2°, 10.1°±0.2°, 21.8°±0.2°, 23.0°±0.2°, 24.3°±0.2°, 24.8°±0.2° and 27.4°±0.2°.
[0032] In one embodiment, the crystalline form has Fig.33 The X-ray powder diffraction pattern is shown.
[0033] In the ninth aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile succinate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 6.8±0.2° and 13.6°±0.2°.
[0034] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 10.2±0.2°, 15.6°±0.2°, 17.5°±0.2° and 20.5°±0.2°.
[0035] In one embodiment, the crystalline form has Fig.37 The X-ray powder diffraction pattern is shown.
[0036] In the tenth aspect, the present application relates to a crystalline form of compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile methanesulfonate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 11.4±0.2°, 12.1°±0.2° and 16.8°±0.2°.
[0037] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 8.7±0.2°, 12.8°±0.2°, 18.2°±0.2° and 19.9°±0.2°.
[0038] In one embodiment, the crystalline form has Fig.41 The X-ray powder diffraction pattern is shown.
[0039] In the eleventh aspect, the present application relates to a crystalline form of compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile methanesulfonate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 11.4±0.2°, 12.1°±0.2° and 16.8°±0.2°.
[0040] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 14.3±0.2°, 15.6°±0.2°, 18.2°±0.2° and 26.1°±0.2°.
[0041] In one embodiment, the crystalline form has Fig.45 The X-ray powder diffraction pattern is shown.
[0042] In the twelfth aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile methanesulfonate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 8.8±0.2°, 15.3°±0.2°, 18.2°±0.2° and 21.5°±0.2°.
[0043] In one embodiment, the X-ray powder diffraction pattern of the crystalline form also includes at least one peak located at a diffraction angle 2θ of 6.1±0.2°, 9.7°±0.2°, 10.4°±0.2°, 11.9°±0.2°, 15.7°±0.2°, 17.5°±0.2°, 19.3°±0.2°, 20.9°±0.2°, 25.6°±0.2° and 26.7°±0.2°.
[0044] In one embodiment, the crystalline form has Fig.49 The X-ray powder diffraction pattern is shown.
[0045] In the thirteenth aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile oxalate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 7.0±0.2°, 16.0°±0.2° and 18.2°±0.2°.
[0046] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 14.0±0.2°, 15.9°±0.2°, 16.7°±0.2°, 19.3°±0.2°, 20.1°±0.2° and 26.2°±0.2°.
[0047] In one embodiment, the crystalline form has Fig.53 The X-ray powder diffraction pattern is shown.
[0048] In the fourteenth aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile ethanesulfonate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 11.4±0.2°, 17.9°±0.2° and 19.1°±0.2°.
[0049] In one embodiment, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 5.7±0.2°, 7.1°±0.2°, 12.1°±0.2°, 14.2°±0.2° and 17.1°±0.2°.
[0050] In one embodiment, the crystalline form has Fig.57 The X-ray powder diffraction pattern is shown.
[0051] In the fifteenth aspect, the present application relates to a crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile 2-hydroxyethanesulfonate, wherein the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 11.4±0.2°, 17.7°±0.2° and 19.1°±0.2°.
[0052] In one embodiment, the X-ray powder diffraction pattern of the crystalline form also includes at least one peak located at a diffraction angle 2θ of 5.7±0.2°, 12.2°±0.2°, 14.2°±0.2°, 15.3°±0.2°, 17.0°±0.2°, 20.9°±0.2°, 22.9°±0.2°, 22.4°±0.2° and 24.7°±0.2°.
[0053] In one embodiment, the crystalline form has Fig.57 The X-ray powder diffraction pattern is shown.
[0054] The present application also relates to a pharmaceutical composition, which comprises the crystal forms or a combination thereof in the first to fifteenth aspects.
[0055] The present application also relates to the use of the crystal forms or combinations thereof or the above-mentioned pharmaceutical compositions in the first to fifteenth aspects in the preparation of drugs for treating JAK kinase-mediated diseases. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The XPRD spectrum of the crystalline form II of the hydrochloride salt of compound A is shown;
[0057] Figure 2 The DSC spectrum of the hydrochloride salt of compound A in Form II is shown;
[0058] Figure 3 The TGA spectrum of the crystalline form II of the hydrochloride salt of compound A is shown;
[0059] Figure 4 The crystalline form II of the hydrochloride salt of compound A is shown 1 H NMR spectrum;
[0060] Figure 5 The XPRD spectrum of the crystalline form I of the hydrochloride salt of compound A is shown;
[0061] Figure 6 The DSC spectrum of the crystalline form I of the hydrochloride salt of compound A is shown;
[0062] Figure 7 The TGA spectrum of the crystalline form I of the hydrochloride salt of compound A is shown;
[0063] Figure 8 The crystalline form I of the hydrochloride salt of compound A is shown 1 H NMR spectrum;
[0064] Fig. 9 The XPRD spectrum of the crystalline form IV of the hydrochloride salt of compound A is shown;
[0065] Fig.10The DSC spectrum of the hydrochloride salt of compound A in Form IV is shown;
[0066] Fig.11 The TGA spectrum of the crystalline form IV of the hydrochloride salt of compound A is shown;
[0067] Fig.12 The crystalline form IV of the hydrochloride salt of compound A is shown 1 H NMR spectrum;
[0068] Fig.13 The XPRD spectrum of the crystalline form I of the sulfate salt of compound A is shown;
[0069] Fig.14 The DSC spectrum of the crystalline form I of the sulfate salt of compound A is shown;
[0070] Fig.15 The TGA spectrum of the crystalline form I of the sulfate salt of compound A is shown;
[0071] Fig.16 The crystalline form I of the sulfate salt of compound A is shown 1 H NMR spectrum;
[0072] Fig.17 The XPRD spectrum of the crystalline form II of the sulfate salt of compound A is shown;
[0073] Fig.18 The DSC spectrum of the crystalline form II of the sulfate salt of compound A is shown;
[0074] Fig.19 The TGA spectrum of the crystalline form II of the sulfate salt of compound A is shown;
[0075] Fig. 20 The crystal form II of the sulfate salt of compound A is shown 1 H NMR spectrum;
[0076] Fig.21 The XPRD spectrum of the crystalline form I of the phosphate salt of compound A is shown;
[0077] Fig. 22 The DSC spectrum of the crystalline form I of the phosphate salt of compound A is shown;
[0078] Fig.23 The TGA spectrum of the crystalline form I of the phosphate salt of compound A is shown;
[0079] Fig.24 The crystalline form I of the phosphate salt of compound A is shown 1 H NMR spectrum;
[0080] Fig.25 The XPRD spectrum of the crystalline form I of the fumarate salt of compound A is shown;
[0081] Fig.26 The DSC spectrum of the crystalline form I of the fumarate salt of compound A is shown;
[0082] Fig. 27 The TGA spectrum of the crystalline form I of the fumarate salt of compound A is shown;
[0083] Fig.28 The crystal form I of the fumarate salt of compound A is shown 1 H NMR spectrum;
[0084] Fig.29 The XPRD pattern of the crystalline form II of the fumarate salt of compound A is shown;
[0085] Fig.30 The DSC spectrum of the crystalline form II of the fumarate salt of compound A is shown;
[0086] Fig.31 The TGA spectrum of the crystalline form II of the fumarate salt of compound A is shown;
[0087] Fig.32 The crystal form II of the fumarate salt of compound A is shown. 1 H NMR spectrum;
[0088] Fig.33 The XPRD spectrum of the crystalline form III of the fumarate salt of compound A is shown;
[0089] Fig.34 The DSC spectrum of the crystalline form III of the fumarate salt of compound A is shown;
[0090] Fig.35 The TGA spectrum of the crystalline form III of the fumarate salt of compound A is shown;
[0091] Fig.36 The crystal form III of the fumarate salt of compound A is shown 1 H NMR spectrum;
[0092] Fig.37 The XPRD pattern of the crystalline form I of the succinate salt of compound A is shown;
[0093] Fig.38 The DSC spectrum of the crystalline form I of the succinate salt of compound A is shown;
[0094] Fig.39 The TGA spectrum of the crystalline form I of the succinate salt of compound A is shown;
[0095] Fig.40 The crystalline form I of the succinate salt of compound A is shown 1 H NMR spectrum;
[0096] Fig.41 The XPRD spectrum of the crystalline form I of the mesylate salt of compound A is shown;
[0097] Fig.42 The DSC spectrum of the crystalline form I of the mesylate salt of compound A is shown;
[0098] Fig.43 The TGA spectrum of the crystalline form I of the mesylate salt of compound A is shown;
[0099] Fig.44 The crystalline form I of the mesylate salt of compound A is shown 1 H NMR spectrum;
[0100] Fig.45 The XPRD spectrum of the crystalline form II of the mesylate salt of compound A is shown;
[0101] Fig.46 The DSC spectrum of the crystalline form II of the mesylate salt of compound A is shown;
[0102] Fig.47 The TGA spectrum of the crystalline form II of the mesylate salt of compound A is shown;
[0103] Fig.48 The crystal form II of the mesylate salt of compound A is shown. 1 H NMR spectrum;
[0104] Fig.49 The XPRD spectrum of the crystalline form III of the mesylate salt of compound A is shown;
[0105] Fig.50 The DSC spectrum of the crystalline form III of the mesylate salt of compound A is shown;
[0106] Fig.51 The TGA spectrum of the crystalline form III of the mesylate salt of compound A is shown;
[0107] Fig.52 The crystalline form III of the mesylate salt of compound A is shown 1 H NMR spectrum;
[0108] Fig.53 The XPRD spectrum of the crystalline form I of the oxalate salt of compound A is shown;
[0109] Fig.54 The DSC spectrum of the crystalline form I of the oxalate salt of compound A is shown;
[0110] Fig.55 The TGA spectrum of the crystalline form I of the oxalate salt of compound A is shown;
[0111] Fig.56The crystalline form I of the oxalate salt of compound A is shown 1 H NMR spectrum;
[0112] Fig.57 The XPRD spectrum of the crystalline form I of the ethanesulfonate salt of compound A is shown;
[0113] Fig.58 The DSC spectrum of the crystalline form I of the ethanesulfonate salt of compound A is shown;
[0114] Fig.59 The TGA spectrum of the crystalline form I of the ethanesulfonate salt of compound A is shown;
[0115] Fig.60 The crystalline form I of the ethanesulfonate salt of compound A is shown 1 H NMR spectrum;
[0116] Fig.61 The XPRD spectrum of the crystalline form I of the 2-hydroxyethanesulfonate salt of compound A is shown;
[0117] Fig.62 The DSC spectrum of the crystalline form I of the 2-hydroxyethanesulfonate salt of compound A is shown;
[0118] Fig.63 The TGA spectrum of the crystalline form I of the 2-hydroxyethanesulfonate salt of compound A is shown;
[0119] Fig.64 The crystalline form I of the 2-hydroxyethanesulfonate salt of compound A is shown. 1 H NMR spectrum;
[0120] Fig.65 The DVS of the hydrochloride salt form II of compound A is shown;
[0121] Fig.66 DVS showing the amorphous form of Compound A;
[0122] Fig.67 A polarizing microscope photograph of the hydrochloride crystal form II of compound A is shown;
[0123] Fig.68 A polarizing microscope photograph showing the amorphous form of Compound A;
[0124] Fig.69 Shows the grinding, tableting and initial XPRD images of the hydrochloride form II of compound A;
[0125] Fig.70 Shows the grinding, tableting and initial XPRD images of the amorphous form of Compound A;
[0126] Fig.71 The XPRD spectrum of the crystalline form IIb of compound A is shown;
[0127] Fig.72 The DSC spectrum of the crystalline form IIb of compound A is shown;
[0128] Fig.73 The TGA spectrum of the crystalline form IIb of compound A is shown;
[0129] Fig.74 The XPRD pattern of the amorphous form of Compound A is shown. DETAILED DESCRIPTION
[0130] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.
[0131] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0132] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0133] In the present application, the compound A referred to refers to 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile, which can also be represented by the following structural formula:
[0134]
[0135] The synthesis method of compound A is disclosed in invention patent CN201711248509.8.
[0136] The term "substantially pure" as used herein when referring to a particular crystalline or amorphous form means that the crystalline or amorphous form contains less than 10% by weight, preferably less than 5% by weight, preferably less than 3% by weight, preferably less than 1% by weight of any other physical form of the compound.
[0137] As used herein, the term "substantially the same" when referring to X-ray diffraction peak positions means that typical peak position and intensity variability is taken into account. For example, those skilled in the art understand that peak positions (2θ) will show some variability, typically as much as 0.1 to 0.2 degrees, depending on the solvent used and the apparatus used to measure diffraction. Further, those skilled in the art understand that relative peak intensities will show instrument-to-instrument variability as well as variability caused by crystallinity, preferred orientation, prepared sample surface, and other factors known to those skilled in the art, and should be considered only as qualitative measurements.
[0138] In the present application, "at least one peak" means 1 peak, 2 peaks, 3 peaks or even all the peaks listed. For example, "at least one peak located at diffraction angles 2θ of 10.6°±0.2°, 11.0°±0.2°, 17.9°±0.2°, 19.1°±0.2°, 19.8°±0.2°, 20.3°±0.2°, 22.3°±0.2°, 25.3°±0.2° and 26.5°±0.2°" means "at least one peak located at diffraction angles 2θ of 10.6 ° ± 0.2°, 11.0° ± 0.2°, 17.9° ± 0.2°, 19.1° ± 0.2°, 19.8° ± 0.2°, 20.3° ± 0.2°, 22.3° ± 0.2°, 25.3° ± 0.2° and 26.5° ± 0.2°”, 1 peak, 2 peaks, 3 peaks, 4 peaks, 5 peaks, 6 peaks, 7 peaks, 8 peaks or 9 peaks.
[0139] The abbreviations used in the present invention are explained as follows:
[0140] XRPD: X-ray powder diffraction
[0141] DSC: Differential Scanning Calorimetry
[0142] TGA: Thermogravimetric analysis
[0143] DVS: Dynamic Water Sorption
[0144] The X-ray powder diffraction pattern of the present invention is obtained by PANalytical Empyrean or X'Pert 3 The X-ray powder diffractometer is used for the collection. The parameters of the X-ray powder diffraction method of the present invention are as follows:
[0145] X-ray source: Cu, Kα
[0146] 1.54060; 1.54439
[0147] Kα2 / Kα1 intensity ratio: 0.50
[0148] Voltage: 45 kilovolts (kV)
[0149] Current: 40 milliamperes (mA)
[0150] Scanning range: from 3.0 to 40.0 degrees.
[0151] The differential scanning calorimetry (DSC) graph of the present invention was collected on a TA Discovery 2500. The method parameters of the differential scanning calorimetry (DSC) of the present invention are as follows:
[0152] Scan rate: 10℃ / min
[0153] Shielding gas: N2.
[0154] The thermogravimetric analysis (TGA) graph of the present invention was collected on a TA Discovery 5500. The method parameters of the thermogravimetric analysis (TGA) of the present invention are as follows:
[0155] Scan rate: 10℃ / min
[0156] Shielding gas: N2.
[0157] The high performance liquid chromatography (HPLC) data in the present invention were collected from Agilent 1260, and the detector used was a diode array detector (DAD).
[0158] The solubility HPLC test method parameters of the present invention are as follows:
[0159] 1. Chromatographic column: ZORBAX Eclipse XDB-C18, 150×4.6mm, 5μm
[0160] 2. Mobile phase: A: 10mM NaH2PO4 aqueous solution (pH = 2.4)
[0161] B: Acetonitrile
[0162] The elution gradient is as follows:
[0163] Time (min) %B 0.0 5.0 7.0 80.0 8.0 80.0 8.1 5.0 12.0 5.0
[0164] 3. Flow rate: 0.85mL / min
[0165] 4. Injection volume: 5μL
[0166] 5. Detection wavelength: 225nm
[0167] 6. Column temperature: 35°C
[0168] 7. Diluent: ACN / mobile phase A1:1
[0169] Unless otherwise specified, the following examples were all operated at room temperature.
[0170] Compound A has an amino group and can form corresponding salts with various acids, such as hydrochloride, sulfate, phosphate, fumarate, succinate, methanesulfonate, oxalate, ethanesulfonate and 2-hydroxyethanesulfonate, etc. These salts are described below.
[0171] Each crystalline form of the salt of Compound A can be characterized by one or more of the following: X-ray powder diffraction (X-ray diffraction peaks at different diffraction angles (2θ)), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), solubility, etc.
[0172] A. Hydrochloride of Compound A
[0173] 1. Crystalline Form II of the Hydrochloride of Compound A
[0174] The crystalline form II of the hydrochloride salt of compound A can be prepared according to the method described in Example 1.
[0175] pass Figure 1 The XPRD pattern shown is used to characterize Form II of the hydrochloride salt of Compound A, which is also shown in Table 1.
[0176] Table 1
[0177] Diffraction angle 2θ d value Relative Strength % 5.2279 16.90 100.00 10.4497 8.47 75.52 11.8150 7.49 9.72 13.1871 6.71 63.60 15.6975 5.65 21.86 17.7135 5.01 91.15 19.9082 4.46 38.91 21.2162 4.19 24.23 22.4064 3.97 37.86 23.1394 3.84 7.82 24.4617 3.64 6.70 25.2277 3.53 7.03 25.9624 3.43 25.03 26.4131 3.37 44.80 26.8216 3.32 14.04 27.4481 3.25 11.85 28.6394 3.12 25.12 29.2344 3.05 6.65
[0178] When differential scanning calorimetry analysis was performed, an endothermic signal was observed at 213.5°C for the hydrochloride crystal form II. Figure 2 shown.
[0179] When subjected to thermogravimetric analysis, hydrochloride Form II has a mass loss gradient of about 0.65% when heated to 120°C. Its TGA is as follows Figure 3 shown.
[0180] High performance liquid chromatography / ion chromatography determined that the molar ratio of hydrochloric acid to free compound A in hydrochloride form II was 1.0.
[0181] 2. Crystalline Form I of the Hydrochloride of Compound A
[0182] The crystalline form I of the hydrochloride salt of compound A can be prepared according to the method described in Example 2.
[0183] pass Figure 5 The XPRD pattern shown is used to characterize Form I of the hydrochloride salt of Compound A, which is also shown in Table 2.
[0184] Table 2
[0185]
[0186]
[0187] When differential scanning calorimetry analysis was performed, endothermic signals were observed at 144.0 and 190.5°C, and exothermic signals (peak temperature) were observed at 152.2°C for hydrochloride Form I. Figure 6 shown.
[0188] When subjected to thermogravimetric analysis, hydrochloride Form I had a mass loss gradient of about 2.11% when heated to 110°C. Its TGA is shown in the attached Figure 7 shown.
[0189] High performance liquid chromatography / ion chromatography determined that the molar ratio of hydrochloric acid to free compound A in hydrochloride form I was 0.7.
[0190] 3. Crystalline Form IV of the Hydrochloride of Compound A
[0191] The crystalline form IV of the hydrochloride salt of compound A can be prepared according to the method described in Example 3.
[0192] pass Fig. 9 The XPRD pattern shown is used to characterize Form IV of the hydrochloride salt of Compound A, which is also shown in Table 3.
[0193] Table 3
[0194]
[0195]
[0196] When differential scanning calorimetry was performed, endothermic signals were observed at 94.5, 167.7, 184.8 and 209.3°C for the hydrochloride crystal form IV. Fig.10 shown.
[0197] When subjected to thermogravimetric analysis, hydrochloride Form IV has a mass loss gradient of about 4.95% when heated to 120°C. Its TGA is shown in the attached Fig.11 shown.
[0198] High performance liquid chromatography / ion chromatography determined that the molar ratio of hydrochloric acid to free compound A in hydrochloride form IV was 2.0.
[0199] B. Crystalline form of the sulfate salt of compound A
[0200] 1. Crystalline Form I of Sulfate Salt of Compound A
[0201] The crystalline form I of the sulfate salt of compound A is a crystalline form that can be prepared according to the method described in Example 4.
[0202] pass Fig.13 The XPRD pattern shown is used to characterize Form I of the sulfate salt of Compound A, which is also shown in Table 4.
[0203] Table 4
[0204] Diffraction angle 2θ d value Relative Strength % 8.5244 10.37 100.00 8.6991 10.17 96.57 12.5480 7.05 29.65 15.6508 5.66 24.73 16.8822 5.25 18.77 18.1370 4.89 26.83 22.0115 4.04 10.45 26.6855 3.34 8.60
[0205] When differential scanning calorimetry was performed, endothermic signals were observed at 72.3 and 166.3 °C for the sulfate salt form I. The DSC data are shown in the attached Fig.14 shown.
[0206] When subjected to thermogravimetric analysis, the sulfate salt Form I has a mass loss gradient of about 1.84% when heated to 120°C. Its TGA is shown in the attached Fig.15 shown.
[0207] High performance liquid chromatography / ion chromatography determined that the molar ratio of sulfuric acid to free compound A in sulfate salt form I was 0.6.
[0208] 2. Crystalline Form II of the Sulfate Salt of Compound A
[0209] The crystalline form II of the sulfate salt of compound A can be prepared according to the method described in Example 5.
[0210] pass Fig.17 The XPRD pattern shown is used to characterize Form II of the sulfate salt of Compound A, which is also shown in Table 5.
[0211] Table 5
[0212]
[0213]
[0214] When differential scanning calorimetry was performed, an endothermic signal was observed at 105.4°C for the sulfate salt form II. Fig.18 shown.
[0215] When subjected to thermogravimetric analysis, the sulfate salt Form II had a mass loss gradient of about 2.47% when heated to 130°C. Its TGA is shown in the attached Fig.19 shown.
[0216] High performance liquid chromatography / ion chromatography determined that the molar ratio of sulfuric acid to free compound A in sulfate salt form II was 0.8.
[0217] C. Crystalline Form I of Phosphate of Compound A
[0218] The crystalline form I of the phosphate salt of compound A is a crystalline form that can be prepared according to the method described in Example 6.
[0219] pass Fig.21 The XPRD patterns shown are used to characterize Form I of the phosphate salt of Compound A, which is also shown in Table 6.
[0220] Table 6
[0221]
[0222]
[0223] When differential scanning calorimetry was performed, endothermic signals were observed at 85.8 and 114.1 °C for the phosphate crystal form I. The DSC data are shown in the attached Fig. 22 shown.
[0224] When subjected to thermogravimetric analysis, the phosphate crystal form I has a mass loss gradient of about 4.34% when heated to 100°C. Its TGA is shown in the attached Fig.23 shown.
[0225] High performance liquid chromatography / ion chromatography determined that the molar ratio of phosphoric acid to free compound A in the phosphate crystal form I was 1.1.
[0226] D. Crystalline form of the fumarate salt of compound A
[0227] 1. Form I of the fumarate salt of compound A
[0228] The crystalline form I of the fumarate salt of compound A is a crystalline form that can be prepared according to the method described in Example 7.
[0229] pass Fig.25 The XPRD pattern shown is used to characterize Form I of the fumarate salt of Compound A, which is also shown in Table 7.
[0230] Table 7
[0231]
[0232]
[0233] When differential scanning calorimetry was performed, endothermic signals were observed at 178.3, 214.7 and 224.8 °C for the fumarate salt form I. Fig.26 shown.
[0234] When subjected to thermogravimetric analysis, the fumarate salt Form I has a mass loss gradient of about 5.22% when heated to 190°C. Its TGA is shown in the attached Fig. 27 shown.
[0235] 2. Form II of the fumarate salt of compound A
[0236] The crystalline form II of the fumarate salt of compound A is a crystalline form that can be prepared according to the method described in Example 8.
[0237] pass Fig.29 The XPRD pattern shown is used to characterize Form II of the fumarate salt of Compound A, which is also shown in Table 8.
[0238] Table 8
[0239] Diffraction angle 2θ d value Relative Strength % 3.1186 28.33 2.21 7.1527 12.36 20.32 8.6033 10.28 31.37 9.8111 9.02 100.00 11.6649 7.59 25.50 12.8401 6.89 11.25 14.3320 6.18 82.50 14.7397 6.01 12.75 16.1725 5.48 24.59 16.6587 5.32 2.66 17.4855 5.07 12.44 18.0257 4.92 8.87 19.6686 4.51 4.05 20.7625 4.28 8.57 21.5808 4.12 13.96 22.7419 3.91 9.18 23.1260 3.85 15.43 26.8843 3.32 20.30 27.9463 3.19 12.45 29.7272 3.01 4.33
[0240] When differential scanning calorimetry was performed, endothermic signals were observed at 163.2, 215.9 and 220.4°C for the fumarate salt form II. Fig.30 shown.
[0241] When subjected to thermogravimetric analysis, the fumarate salt Form II had a mass loss gradient of about 8.10% when heated to 170°C. Its TGA is shown in the attached Fig.31 shown.
[0242] 3. Form III of the fumarate salt of compound A
[0243] The crystalline form III of the fumarate salt of compound A can be prepared according to the method described in Example 9.
[0244] pass Fig.33 The XPRD pattern shown is used to characterize Form III of the fumarate salt of Compound A, which is also shown in Table 9.
[0245] Table 9
[0246] Diffraction angle 2θ d value Relative Strength % 7.1231 12.41 15.00 9.1584 9.66 68.28 10.0775 8.78 12.84 12.9619 6.83 8.04 14.2462 6.22 100.00 15.3920 5.76 7.15 16.7887 5.28 4.81 17.2615 5.14 2.59 17.7397 5.00 5.20 18.0502 4.91 3.55 19.9675 4.45 4.74 21.2792 4.18 8.31 21.7891 4.08 14.48 22.4940 3.95 7.94 22.9987 3.87 16.00 24.2875 3.66 12.85 24.8492 3.58 11.59 26.0906 3.42 2.53 27.3605 3.26 12.25 28.6302 3.12 1.39 30.0684 2.97 5.06 33.7572 2.66 1.90 34.9651 2.57 1.35 36.0856 2.49 2.10
[0247] When differential scanning calorimetry was performed, endothermic signals were observed at 164.3 and 211.7 °C for the fumarate salt form III. Fig.34 shown.
[0248] When subjected to thermogravimetric analysis, the fumarate salt Form III had a mass loss gradient of about 5.77% when heated to 180°C. Its TGA is shown in the attached Fig.35 shown.
[0249] E. Crystalline Form I of the Succinate Salt of Compound A
[0250] The crystalline form I of the succinate salt of compound A is a crystalline form that can be prepared according to the method described in Example 10.
[0251] pass Fig.37 The XPRD patterns shown are used to characterize Form I of the succinate salt of Compound A, which is also shown in Table 10.
[0252] Table 10
[0253]
[0254]
[0255] When differential scanning calorimetry was performed, endothermic signals were observed at 174.1 and 219.0 °C for the succinate salt form I. The DSC data are shown in the attached Fig.38 shown.
[0256] When subjected to thermogravimetric analysis, the succinate salt Form I had a mass loss gradient of about 2.26% when heated to 160°C. Its TGA is shown in the attached Fig.39 shown.
[0257] F. Crystalline form of the mesylate salt of compound A
[0258] 1. Crystalline Form I of the Methanesulfonate of Compound A
[0259] The crystalline form I of the mesylate salt of compound A can be prepared according to the method described in Example 11.
[0260] pass Fig.41 The XPRD pattern shown is used to characterize Form I of the mesylate salt of Compound A, which is also shown in Table 11.
[0261] Table 11
[0262] Diffraction angle 2θ d value Relative Strength % 4.2424 20.83 10.35 5.8189 15.19 12.15 8.6514 10.22 28.38 11.4330 7.74 66.45 12.1147 7.31 100.00 12.8227 6.90 33.60 15.1842 5.84 11.83 16.7891 5.28 58.43 18.2288 4.87 24.15 18.8166 4.72 18.57 19.9113 4.46 27.72 23.0273 3.86 7.85 24.5876 3.62 7.07 26.8560 3.32 8.89 28.9372 3.09 5.54
[0263] When differential scanning calorimetry was performed, endothermic signals were observed at 70.6, 118.7 and 153.1°C for the mesylate salt Form I. Fig.42 shown.
[0264] When subjected to thermogravimetric analysis, the mesylate salt Form I had a mass loss gradient of about 1.86% when heated to 130°C. Its TGA is shown in the attached Fig.43 shown.
[0265] 2. Crystalline Form II of the Methanesulfonate of Compound A
[0266] The crystalline form II of the mesylate salt of compound A can be prepared according to the method described in Example 12.
[0267] pass Fig.45 The XPRD pattern shown is used to characterize Form II of the mesylate salt of Compound A, which is also shown in Table 12.
[0268] Table 12
[0269] Diffraction angle 2θ d value Relative Strength % 5.6897 15.53 74.37 7.1232 12.41 13.84 11.3592 7.79 100.00 14.2798 6.20 28.79 15.5852 5.69 39.82 16.3271 5.43 16.54 17.3054 5.12 20.36 18.2130 4.87 41.05 19.1410 4.64 46.17 19.8447 4.47 10.24 21.3109 4.17 12.22 22.7911 3.90 7.12 23.7548 3.75 4.17 24.4024 3.65 11.81 24.9955 3.56 11.27 26.1167 3.41 22.24 26.5956 3.35 12.92 28.6650 3.11 4.52 34.7307 2.58 5.36
[0270] When differential scanning calorimetry was performed, an endothermic signal was observed at 170.4°C for the mesylate salt Form II. Fig.46 shown.
[0271] When subjected to thermogravimetric analysis, the mesylate salt Form II had a mass loss gradient of about 1.37% when heated to 120°C. Its TGA is shown in the attached Fig.47 shown.
[0272] 3. Crystalline Form III of the Methanesulfonate of Compound A
[0273] The crystalline form III of the mesylate salt of compound A can be prepared according to the method described in Example 13.
[0274] pass Fig.49 The XPRD pattern shown is used to characterize Form III of the mesylate salt of Compound A, which is also shown in Table 13.
[0275] Table 13
[0276]
[0277]
[0278] When differential scanning calorimetry was performed, endothermic signals were observed at 94.9 and 142.5 °C for the mesylate salt Form III. Fig.50 shown.
[0279] When subjected to thermogravimetric analysis, the mesylate salt Form III had a mass loss gradient of about 2.25% when heated to 120°C. Its TGA is shown in the attached Fig.51 shown.
[0280] G. Crystalline Form I of the Oxalate of Compound A
[0281] The crystalline form I of the oxalate salt of compound A can be prepared according to the method described in Example 14.
[0282] pass Fig.53 The XPRD pattern shown is used to characterize Form I of the oxalate salt of Compound A, which is also shown in Table 14.
[0283] Table 14
[0284]
[0285]
[0286] When differential scanning calorimetry was performed, an endothermic signal was observed at 190.5°C for the oxalate salt form I. Fig.54 shown.
[0287] When subjected to thermogravimetric analysis, the oxalate crystal form I has a mass loss gradient of about 1.42% when heated to 120°C. Its TGA is shown in the attached Fig.55 shown.
[0288] High performance liquid chromatography / ion chromatography determined that the molar ratio of oxalic acid to free compound A in oxalate form I was 1.1.
[0289] H. Crystalline Form I of the Ethysulfonate of Compound A
[0290] The crystalline form I of the ethanesulfonate salt of compound A can be prepared according to the method described in Example 14.
[0291] pass Fig.57 The XPRD pattern shown is used to characterize Form I of the ethanesulfonate salt of Compound A, which is also shown in Table 15.
[0292] Table 15
[0293]
[0294]
[0295] When differential scanning calorimetry analysis was performed, an endothermic signal was observed at 185.6°C for the ethanesulfonate salt Form I. The DSC of the ethanesulfonate salt Form I is shown in the attached Fig.58 shown.
[0296] When subjected to thermogravimetric analysis, the ethanesulfonate salt Form I had a mass loss gradient of about 0.22% when heated to 120°C. Its TGA is shown in the attached Fig.59 shown.
[0297] I. Crystalline Form I of 2-Hydroxyethanesulfonate of Compound A
[0298] The crystalline form I of the 2-hydroxyethanesulfonate salt of compound A is a crystalline form that can be prepared according to the method described in Example 14.
[0299] pass Fig.61 The XPRD pattern shown is used to characterize Form I of the 2-hydroxyethanesulfonate salt of Compound A, which is also shown in Table 16.
[0300] Table 16
[0301]
[0302]
[0303] When differential scanning calorimetry analysis was performed, an endothermic signal was observed at 139.1°C for 2-hydroxyethanesulfonate Form I. Fig.62 shown.
[0304] When subjected to thermogravimetric analysis, the 2-hydroxyethanesulfonate salt Form I had a mass loss gradient of about 0.55% when heated to 110°C. Its TGA is shown in the attached Fig.63 shown.
[0305] II. Pharmaceutical compositions and uses
[0306] Compound A belongs to the JAK class of small molecule non-receptor tyrosine kinase inhibitors, which can be used to treat Janus kinase (JAK kinase) mediated diseases. For example, JAK kinase mediated diseases can be tumors or autoimmune diseases. Further, JAK kinase mediated diseases include but are not limited to tumor diseases such as leukemia, lymphoma, myeloproliferative tumors, myelodysplastic syndrome; also include but are not limited to rheumatoid arthritis, psoriatic arthritis, autoimmune skin diseases and other autoimmune diseases.
[0307] Furthermore, diseases mediated by JAK kinases may include, but are not limited to, autoimmune skin diseases such as psoriasis, atopic dermatitis, vitiligo, pruritus, scleroderma, alopecia areata, alopecia totalis, alopecia universalis, and androgenic alopecia.
[0308] The active agent of the present invention (i.e., a polymorph of a salt of Compound A herein or a solid form comprising two or more of the polymorphs) can be formulated into a pharmaceutical composition suitable for medical use in mammals. Any suitable route of administration can be used to provide an effective dose of any polymorph of a salt of Compound A to a patient. For example, dosage forms include capsules, tablets, dispersions, suspensions, ointments, etc. In all dosage forms, the polymorphs of the salt of Compound A can be mixed with other suitable ingredients. The composition can be conveniently present in a unit dosage form and can be prepared by any method known in the pharmaceutical field. The pharmaceutical composition of the present invention comprises a therapeutically effective amount of an active agent and one or more inert pharmaceutically acceptable carriers, and optionally any other therapeutic ingredients, stabilizers or the like. From the perspective of compatibility with other ingredients of the preparation and not excessively damaging its receptor, the carrier must be pharmaceutically acceptable. The composition may further include diluents, buffers, binders, disintegrants, thickeners, lubricants, preservatives (including antioxidants), flavoring agents, taste masking agents, inorganic salts (e.g., sodium chloride), antimicrobial agents (e.g., benzalkonium chloride, etc.), sweeteners, antistatic agents, surfactants, sorbitan esters, lipids, etc. The active agents of the present invention may be formulated into compositions including those suitable for oral, rectal, topical, nasal, ocular, or parenteral (including intraperitoneal, intravenous, subcutaneous or intramuscular injection) administration.
[0309] The following examples will further illustrate the preparation of polymorphs of different salts of the present invention, but are not intended to limit the present invention.
[0310] Preparatory Example 1: Preparation and Characterization of Form IIb of Compound A
[0311] The crystalline form IIb of compound A can be prepared according to the following process:
[0312] In a 100 mL flask, add 6.2 g of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile and 25 mL of N,N-dimethylformamide, stir to dissolve, filter to remove insoluble matter, add 50 mL of purified water to the filtrate, stir to crystallize, filter, and dry the resulting solid at 55-60°C to constant weight to obtain 5.6 g of an off-white solid with a yield of 88.9%.
[0313] The crystal form IIb was characterized by X-ray powder diffraction, TGA, and DSC. The X-ray powder diffraction data of the crystal form IIb are shown in Table 17 and Fig.71 The DSC spectrum is shown in Fig.72 As shown, the crystal form IIb has an endothermic peak between 50 and 200°C, and an endothermic peak near 221.5°C; the dehydration temperature is about 120.7°C, and the melting temperature is 220.2°C. The TGA spectrum is shown in Fig.73 As shown, it shows a weight loss of about 2.2% at 50-150°C.
[0314] Table 17
[0315]
[0316] Preparatory Example 2: Preparation and Characterization of Amorphous Form of Compound A
[0317] Weigh 103.7 mg of compound A sample into a 50 mL flask, add 10 mL of acetone to dissolve, filter into another 50 mL flask with a PTFE filter membrane with a pore size of 0.45 μm, and rotary evaporate the solvent to obtain a solid.
[0318] Using Cu-Kα radiation, its X-ray powder diffraction pattern is basically as follows Fig.74 As shown, the lack of sharp X-ray powder diffraction peaks indicates that it is amorphous.
[0319] Example 1: Preparation and characterization of hydrochloride salt form II
[0320] Preparation steps of the hydrochloride salt form II sample (829723-03-A19): Weigh 20.1 mg of the form IIb sample of compound A into an HPLC bottle, add 0.25 mL of methanol to make a solution; take 37.5 μL of hydrochloric acid (4M hydrochloric acid ethyl acetate solution, 3.0 equivalents) into an HPLC bottle, and add 0.25 mL of methanol to make a solution; under magnetic stirring (750 rpm), add the prepared hydrochloric acid solution dropwise to the compound A solution; magnetically stir at room temperature for 3 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0321] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR spectroscopy.
[0322] The X-ray powder diffraction data of the crystal form are shown in Table 1 and Figure 1 As shown; DSC spectrum as Figure 2 As shown, an endothermic signal was observed at 213.5°C; the TGA spectrum is shown Figure 3 As shown, it is shown that when heated to 120°C, there is a mass loss gradient of about 0.65%.
[0323] Liquid state NMR hydrogen spectrum was measured in DMSO-d6, and no residual solvent was observed in the hydrochloride crystal form II. 1 H NMR spectrum Figure 4 shown.
[0324] Example 2: Preparation and characterization of hydrochloride salt form I
[0325] Preparation steps of the hydrochloride form I sample (829723-03-A1): Weigh 20.2 mg of the form IIb sample of compound A into an HPLC bottle, add 0.25 mL of methanol to make a solution; take 13.7 μL of hydrochloric acid (4M hydrochloric acid ethyl acetate solution, 1.1 equivalents) into an HPLC bottle, and add 0.25 mL of methanol to make a solution; under magnetic stirring (750 rpm), add the prepared hydrochloric acid solution dropwise to the compound A solution; magnetically stir at room temperature for 3 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0326] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR spectroscopy.
[0327] The X-ray powder diffraction data of the crystal form are shown in Table 2 and Figure 5 As shown; DSC spectrum as Figure 6 As shown, endothermic signals were observed at 144.0 and 190.5°C, and exothermic signals were observed at 152.2°C (peak temperature); the TGA spectrum is shown Figure 7As shown, when heated to 110°C, there is a mass loss gradient of about 2.11%.
[0328] Liquid state NMR hydrogen spectrum was measured in DMSO-d6, and no residual solvent was observed in the hydrochloride crystal form I. 1 H NMR spectrum is attached Figure 8 shown.
[0329] Example 3: Preparation and characterization of hydrochloride salt form IV
[0330] Preparation steps of the hydrochloride salt form IV sample (829723-08-A3): Weigh 19.7 mg of the form IIb sample of compound A into an HPLC bottle, add 0.25 mL of ethyl acetate to make a solution; take 50.0 μL of hydrochloric acid (4M hydrochloric acid ethyl acetate solution, 4.0 equivalents) into an HPLC bottle, and add 0.25 mL of ethyl acetate to make a solution; under magnetic stirring (750 rpm), add the prepared hydrochloric acid solution dropwise to the compound A solution; magnetically stir at room temperature for 5 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature overnight.
[0331] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR spectroscopy.
[0332] The X-ray powder diffraction data of the crystal form are shown in Table 3 and Fig. 9 As shown; DSC spectrum as Fig.10 As shown, endothermic signals were observed at 94.5, 167.7, 184.8 and 209.3°C; the TGA spectrum is shown in Fig.11 As shown, it is shown that when heated to 120°C, there is a mass loss gradient of about 4.95%.
[0333] Liquid state NMR hydrogen spectrum was measured in DMSO-d6, and the signal of residual solvent ethyl acetate was observed in hydrochloride crystal form IV, and the molar ratio of the free compound A was 0.1 (1.8wt%). 1 H NMR spectrum is attached Fig.12 shown.
[0334] Example 4: Preparation and characterization of sulfate crystal form I
[0335] Preparation steps of sulfate form I sample (829723-03-A2): Weigh 20.1 mg of form IIb sample of compound A into an HPLC bottle, add 0.25 mL of methanol to make a solution; take 5.0 mg of sulfuric acid (98%, 1.0 equivalent) into an HPLC bottle, and add 0.25 mL of methanol to make a solution; under magnetic stirring (750 rpm), add the prepared sulfuric acid solution dropwise to the compound A solution; magnetically stir at room temperature for 3 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0336] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR spectroscopy.
[0337] The X-ray powder diffraction data of the crystal form are shown in Table 4 and Fig.13 As shown; DSC spectrum as Fig.14 As shown, endothermic signals were observed at 72.3 and 166.3°C; the TGA spectrum is shown Fig.15 As shown, it is shown that when heated to 120°C, there is a mass loss gradient of about 1.84%.
[0338] Liquid state H NMR spectrum was measured in DMSO-d6, and no residual solvent signal was observed in sulfate crystal form I. 1 HNMR spectrum is attached Fig.16 shown.
[0339] Example 5: Preparation and characterization of sulfate crystal form II
[0340] Preparation steps of sulfate form II sample (829723-03-B2): Weigh 20.1 mg of form IIb sample of compound A into an HPLC bottle, add 0.25 mL of ethyl acetate to make a solution; take 5.0 mg of sulfuric acid (98%, 1.0 equivalent) into an HPLC bottle, and add 0.25 mL of ethyl acetate to make a solution; under magnetic stirring (750 rpm), add the prepared sulfuric acid solution dropwise to the compound A solution; magnetically stir at room temperature for 3 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0341] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR spectroscopy.
[0342] The X-ray powder diffraction data of the crystal form are shown in Table 5 and Fig.17 As shown; DSC spectrum as Fig.18 As shown, an endothermic signal was observed at 105.4°C; the TGA spectrum is shown Fig.15 As shown, it is shown that when heated to 130°C, there is a mass loss gradient of about 2.47%.
[0343] Liquid state NMR hydrogen spectrum was measured in DMSO-d6, and the signal of residual solvent EtOAc was observed in sulfate crystal form II, and the molar ratio of EtOAc to free compound A was 0.08 (1.6 wt%). 1 H NMR spectrum is attached Fig. 20 shown.
[0344] Example 6: Preparation and characterization of phosphate crystal form I
[0345] Preparation steps of phosphate form I sample (829723-03-B4): Weigh 19.8 mg of form IIb sample of compound A into an HPLC bottle, add 0.25 mL of ethyl acetate to make a solution; take 3.2 μL of phosphoric acid (85%, 1.0 equivalent) into an HPLC bottle, and add 0.25 mL of ethyl acetate to make a solution; under magnetic stirring (750 rpm), add the prepared phosphoric acid solution dropwise to the compound A solution; magnetically stir at room temperature for 3 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0346] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR spectroscopy.
[0347] The X-ray powder diffraction data of the crystal form are shown in Table 6 and Fig.21 As shown; DSC spectrum as Fig. 22 As shown, endothermic signals were observed at 85.8 and 114.1°C; the TGA spectrum is shown Fig.23 As shown, it is shown that when heated to 100°C, there is a mass loss gradient of about 4.34%.
[0348] Liquid state NMR hydrogen spectrum was measured in DMSO-d6, and the signal of residual solvent EtOAc was observed in phosphate crystal form I, and the molar ratio of EtOAc to free compound A was 0.2 (3.7 wt%). 1 H NMR spectrum is attached Fig.24 shown.
[0349] Example 7: Preparation and Characterization of Fumarate Form I
[0350] Preparation steps of the fumarate salt form I sample (829723-03-A5): Weigh 19.7 mg of the form IIb sample of compound A into an HPLC bottle, weigh 5.9 mg of fumaric acid (1.0 equivalent) and add it to the same bottle, add 0.5 mL of methanol; magnetically stir at room temperature for 4 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0351] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR. The X-ray powder diffraction data of the crystal form are shown in Table 7 and Fig.25 As shown; DSC spectrum as Fig.26 As shown, endothermic signals were observed at 178.3, 214.7 and 224.8°C; the TGA spectrum is shown in Fig. 27 As shown, it is shown that when heated to 190°C, there is a mass loss gradient of about 5.22%.
[0352] Liquid state nuclear magnetic hydrogen spectrum was measured in DMSO-d6, and the signal of fumaric acid was observed in the fumarate salt crystal form I, and the molar ratio with the free compound A was 0.5, and the signal of residual solvent methanol was not observed. 1 H NMR spectrum is attached Fig.28 shown.
[0353] Example 8: Preparation and Characterization of Fumarate Form II
[0354] Preparation steps of the fumarate salt form II sample (829723-03-B5): Weigh 20.3 mg of the form IIb sample of compound A into an HPLC bottle, weigh 6.0 mg of fumaric acid (1.0 equivalent) and add it to the same bottle, add 0.5 mL of ethyl acetate; magnetically stir at room temperature for 4 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0355] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR. The X-ray powder diffraction data of the crystal form are shown in Table 8 and Fig.29 As shown; DSC spectrum as Fig.30 As shown, endothermic signals were observed at 178.3, 214.7 and 224.8°C; the TGA spectrum is shown in Fig.31 As shown, it is shown that when heated to 190°C, there is a mass loss gradient of about 5.22%.
[0356] Liquid state nuclear magnetic hydrogen spectrum was measured in DMSO-d6. The signal of fumaric acid was observed in the fumarate salt crystal form II, and the molar ratio of fumaric acid to the free compound A was 1.0. The signal of residual solvent EtOAc was observed, and the molar ratio of EtOAc to the free compound A was 0.4 (6.1 wt%). 1 H NMR spectrum is attached Fig.32 shown.
[0357] Example 9: Preparation and Characterization of Fumarate Form III
[0358] Preparation steps of the fumarate salt form III sample (829723-03-C5): Weigh 20.2 mg of the form IIb sample of compound A into an HPLC bottle, weigh 5.8 mg of fumaric acid (1.0 equivalent) and add it to the same bottle, add 0.5 mL of acetone; magnetically stir at room temperature for 4 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0359] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state H-NMR. The X-ray powder diffraction data of the crystal form are shown in Table 9 and Fig.33 As shown; DSC spectrum as Fig.34 As shown, endothermic signals were observed at 164.3 and 211.7°C; the TGA spectrum is shown Fig.35 As shown, it is shown that when heated to 180°C, there is a mass loss gradient of about 5.77%.
[0360] Liquid state nuclear magnetic hydrogen spectrum was measured in DMSO-d6. The signal of fumaric acid was observed in the fumarate salt form III, and the molar ratio of fumaric acid to the free compound A was 0.5. The signal of residual solvent acetone was observed, and the molar ratio of acetone to the free compound A was 0.4 (4.8wt%). 1 H NMR spectrum is attached Fig.36 shown.
[0361] Example 10: Preparation and characterization of succinate salt form I
[0362] Preparation steps of succinate salt form I sample (829723-03-B9): Weigh 20.1 mg of form IIb sample of compound A into an HPLC bottle, weigh 5.8 mg of succinic acid (1.0 equivalent) and add it to the same bottle, add 0.5 mL of ethyl acetate; magnetically stir at room temperature for 4 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0363] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state nuclear magnetic hydrogen spectrum. The X-ray powder diffraction data of the crystal form are shown in Table 10 and Fig.37 As shown; DSC spectrum as Fig.38 As shown, endothermic signals were observed at 174.1 and 219.0°C; the TGA spectrum is shown Fig.39 As shown, it is shown that when heated to 160°C, there is a mass loss gradient of about 2.26%.
[0364] Liquid state NMR hydrogen spectrum was measured in DMSO-d6. The signal of succinic acid was observed in the succinate salt form I, and the molar ratio of succinic acid to the free compound A was 0.5. The signal of residual solvent EtOAc was observed, and the molar ratio of EtOAc to the free compound A was 0.01 (0.2 wt%).1 H NMR spectrum is attached Fig.40 shown.
[0365] Example 11: Preparation and characterization of mesylate salt form I
[0366] Preparation steps of the mesylate salt form I sample (829723-03-A12): Weigh 19.7 mg of the form IIb sample of compound A into an HPLC bottle, add 0.25 mL of methanol to make a solution; weigh 4.8 mg of methanesulfonic acid (1.0 equivalent) into an HPLC bottle, and add 0.25 mL of methanol to make a solution; under magnetic stirring (750 rpm), add the prepared methanesulfonic acid solution dropwise to the compound A solution; magnetically stir at room temperature for 3 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0367] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state nuclear magnetic hydrogen spectrum. The X-ray powder diffraction data of the crystal form are shown in Table 11 and Fig.41 As shown; DSC spectrum as Fig.42 As shown, endothermic signals were observed at 70.6, 118.7 and 153.1°C; the TGA spectrum is shown Fig.43 As shown, it is shown that when heated to 130°C, there is a mass loss gradient of about 1.86%.
[0368] Liquid state NMR hydrogen spectrum was measured in DMSO-d6, and the signal of methanesulfonic acid was observed in the mesylate salt form I, and the molar ratio of methanesulfonic acid to the free compound A was 0.8, and no signal of residual solvent methanol was observed. 1 H NMR spectrum is attached Fig.44 shown.
[0369] Example 12: Preparation and characterization of mesylate salt form II
[0370] Preparation steps of the mesylate salt form II sample (829723-03-B12): Weigh 20.1 mg of the form IIb sample of compound A into an HPLC bottle, add 0.25 mL of ethyl acetate to make a solution; weigh 4.8 mg of methanesulfonic acid (1.0 equivalent) into an HPLC bottle, and add 0.25 mL of ethyl acetate to make a solution; under magnetic stirring (750 rpm), the prepared methanesulfonic acid solution was added dropwise to the compound A solution; gelation of the system was observed, and it was transferred to temperature cycle magnetic stirring for 3 days (50°C~5°C, heating rate 4.5°C / min, constant temperature at 50°C for 2 hours, cooling rate 0.1°C / min, constant temperature at 5°C for 2 hours), solid precipitated, centrifuged at room temperature (10000 rpm, 2 minutes) and the supernatant was discarded, and the solid was vacuum dried at room temperature for 3 days.
[0371] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state nuclear magnetic hydrogen spectrum. The X-ray powder diffraction data of the crystal form are shown in Table 12 and Fig.45 As shown; DSC spectrum as Fig.46 As shown, an endothermic signal was observed at 170.4°C; the TGA spectrum is shown Fig.47 As shown, it is shown that when heated to 120°C, there is a mass loss gradient of about 1.37%.
[0372] Liquid state H NMR spectrum was measured in DMSO-d6. The signal of methanesulfonic acid was observed in the mesylate salt form II, and the molar ratio with the free compound A was 1.0. No signal of residual solvent EtOAc was observed. 1 H NMR spectrum is attached Fig.48 shown.
[0373] Example 13: Preparation and characterization of mesylate salt form III
[0374] Preparation steps of the mesylate salt form III sample (829723-03-B20): Weigh 19.8 mg of the form IIb sample of compound A into an HPLC bottle, add 0.25 mL of ethyl acetate to make a solution; weigh 14.4 mg of methanesulfonic acid (3.0 equivalents) into an HPLC bottle, and add 0.25 mL of ethyl acetate to make a solution; under magnetic stirring (750 rpm), the prepared methanesulfonic acid solution was added dropwise to the compound A solution; gelation of the system was observed, and it was transferred to temperature cycle magnetic stirring for 3 days (50°C~5°C, heating rate 4.5°C / min, constant temperature at 50°C for 2 hours, cooling rate 0.1°C / min, constant temperature at 5°C for 2 hours), solid precipitated, centrifuged at room temperature (10000 rpm, 2 minutes) and the supernatant was discarded, and the solid was vacuum dried at room temperature for 3 days.
[0375] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state nuclear magnetic hydrogen spectrum. The X-ray powder diffraction data of the crystal form are shown in Table 13 and Fig.49 As shown; DSC spectrum as Fig.50 As shown, endothermic signals were observed at 94.9 and 142.5°C; the TGA spectrum is shown Fig.51 As shown, it is shown that when heated to 120°C, there is a mass loss gradient of about 2.25%.
[0376] Liquid state nuclear magnetic hydrogen spectrum was measured in DMSO-d6. The signal of methanesulfonic acid was observed in the mesylate salt form III, and the molar ratio of methanesulfonic acid to the free compound A was 2.2. The signal of residual solvent ethyl acetate was observed, and the molar ratio of ethyl acetate to the free compound A was 0.01 (0.1wt%). 1 H NMR spectrum is attached Fig.52 shown.
[0377] Example 14: Preparation and characterization of oxalate crystal form I
[0378] Preparation steps of oxalate form I sample (829723-03-B14): Weigh 20.1 mg of form IIb sample of compound A into an HPLC bottle, weigh 6.2 mg of oxalic acid (1.0 equivalent) and add it to the same bottle, add 0.5 mL of ethyl acetate; magnetically stir at room temperature for 4 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid under vacuum at room temperature for 3 days.
[0379] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state nuclear magnetic hydrogen spectrum. The X-ray powder diffraction data of the crystal form are shown in Table 14 and Fig.53 As shown; DSC spectrum as Fig.54 As shown, an endothermic signal was observed at 190.5°C; the TGA spectrum is shown Fig.55 As shown, it is shown that when heated to 120°C, there is a mass loss gradient of about 1.42%.
[0380] Liquid state H NMR spectrum was measured in DMSO-d6, and no signal of residual solvent ethyl acetate was observed in oxalate crystal form I. 1 H NMR spectrum is attached Fig.56 shown.
[0381] Example 15: Preparation and characterization of ethanesulfonate salt form I
[0382] Preparation steps of ethanesulfonate salt form I sample (829723-03-A16): Weigh 19.9 mg of form IIb sample of compound A into an HPLC bottle, add 0.25 mL of methanol to make a solution; weigh 5.6 mg of ethanesulfonic acid (1.0 equivalent) into an HPLC bottle, and add 0.25 mL of methanol to make a solution; under magnetic stirring (750 rpm), add the prepared ethanesulfonic acid solution dropwise to the compound A solution; observe that the system is clear, transfer to 5°C and stir for 3 days, centrifuge at room temperature (10000 rpm, 2 minutes) and discard the supernatant, and dry the solid in vacuum at room temperature for 3 days.
[0383] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state nuclear magnetic hydrogen spectrum. The X-ray powder diffraction data of the crystal form are shown in Table 15 and Fig.57 As shown; DSC spectrum as Fig.58 As shown, an endothermic signal was observed at 185.6°C; the TGA spectrum is shown Fig.59 As shown, it is shown that when heated to 120°C, there is a mass loss gradient of about 0.22%.
[0384] Liquid state NMR hydrogen spectrum was measured in DMSO-d6, and the signal of ethanesulfonic acid was observed in ethanesulfonic acid salt form I, and the molar ratio with free compound A was 1.0, and the signal of residual solvent methanol was not observed. 1 H NMR spectrum is attached Fig.60 shown.
[0385] Example 16: Preparation and Characterization of 2-Hydroxyethanesulfonate Form I
[0386] Preparation steps of 2-hydroxyethanesulfonate salt form I sample (829723-08-A6): Weigh 20.2 mg of form IIb sample of compound A into an HPLC bottle, add 0.25 mL of methanol to make a solution; weigh 13.5 mg of 2-hydroxyethanesulfonic acid (80%, 1.7 equivalents) into an HPLC bottle, and add 0.25 mL of methanol to make a solution; under magnetic stirring (750 rpm), the prepared 2-hydroxyethanesulfonic acid solution was added dropwise to the compound A solution; the system was observed to be clear, and after 1.2 mL of methyl tert-butyl ether was added dropwise to the clear solution, the system became gelled, and solid precipitation was observed when stirred at room temperature for 5 days. The solution was centrifuged at room temperature (10000 rpm, 2 minutes) and the supernatant was discarded, and the solid was vacuum dried at room temperature for 1 day.
[0387] The crystal form was characterized by X-ray powder diffraction, TGA, DSC and liquid state nuclear magnetic hydrogen spectrum. The X-ray powder diffraction data of the crystal form are shown in Table 16 and Fig.61 As shown; DSC spectrum as Fig.62 As shown, an endothermic signal was observed at 139.1°C; the TGA spectrum is shown Fig.63 As shown, it is shown that when heated to 110°C, there is a mass loss gradient of about 0.55%.
[0388] Liquid state nuclear magnetic hydrogen spectrum was measured in DMSO-d6. The signal of 2-hydroxyethanesulfonic acid was observed in 2-hydroxyethanesulfonate salt form I, and the molar ratio of 2-hydroxyethanesulfonic acid to free compound A was 1.3. The signal of residual solvent methyl tert-butyl ether was observed, and the molar ratio of methyl tert-butyl ether to free compound A was 0.01 (0.2wt%). 1 H NMR spectrum is attached Fig.64 shown.
[0389] Test Case
[0390] 1: Hygroscopicity
[0391] About 20-50 mg of the hydrochloride crystal form II sample prepared in Example 1 and the amorphous sample of the raw material drug (prepared in Preparatory Example 2) were weighed for dynamic moisture sorption (DVS) testing, which was collected on the DVS Intrinsic Plus of SMS (Surface Measurement Systems).
[0392] The experimental results are shown in Table 18. The DVS of hydrochloride crystal form II is shown in the attached Fig.65 As shown, the amorphous DVS is shown in the attached Fig.66 As shown in the figure, the hydrochloride crystal form II showed no crystalline change after the DVS test, and the amorphous sample turned into crystal form IIb after the test.
[0393] Table 18
[0394]
[0395] Compared with the amorphous compound A, the hydrochloride crystal form II of the present invention has a smaller moisture absorption weight gain with increasing humidity and better physical stability.
[0396] 2: Comparative study of solid-state physical and chemical stability
[0397] About 2 to 3 mg of the hydrochloride crystal form II (initial purity 99.63%) obtained in Example 1 of the present invention was weighed, and placed in an oven at 80°C with a closed mouth. After one day, samples were taken for XRPD and HPLC measurement. After one week, samples were taken for XRPD and HPLC measurement.
[0398] Weigh about 2 to 3 mg of the amorphous form (initial purity 99.74%) obtained in Preparatory Example 2 of the present invention, place it in an oven at 80°C with the lid closed, take a sample after 1 day to measure XRPD and HPLC, and place it in a stabilization box at 25°C / 60%RH and 40°C / 75%RH with the lid open, take a sample after 1 month to measure XRPD and HPLC.
[0399] The experimental results are shown in Table 19. The results show that the hydrochloride crystal form II did not change significantly after being placed under 25°C / 60%RH, 40°C / 75%RH and 80°C; and after being placed under 40°C / 75%RH for one week, the purity did not decrease significantly. The amorphous form did not change significantly after being placed under 25°C / 60%RH, 40°C / 75%RH and 80°C, but the purity decreased significantly under 40°C / 75%RH and 80°C.
[0400] Table 19
[0401]
[0402] *Relative purity = test sample HPLC purity / starting sample HPLC purity × 100%
[0403] 3: Solubility comparison study
[0404] The hydrochloride crystal form II sample prepared in Example 1, the free base amorphous sample (prepared in Preparative Example 2), and the crystal form IIb of compound A (prepared in Preparative Example 1) were weighed respectively, and prepared into a suspension with H2O, simulated body fluid (SBF), propylene glycol and PEG-400, and stirred and mixed at 25°C with a feed concentration of 10 mg / mL (for the PEG-400 system, the feed concentration was adjusted to >150 mg / mL), and the solubility of each sample was measured at a point taken after 24 hours. After sampling, centrifugation (12000 rpm, 2 min) and filtration (0.45 μm PTFE membrane) were performed, and the HPLC concentration of the filtrate was measured, and the solid sample after centrifugation was tested by XRPD.
[0405] The experimental results are shown in Table 20. The results show that compared with the amorphous form, the hydrochloride crystal form II of the present invention has better solubility in water, propylene glycol and SBF (pH=7.4 buffer).
[0406] Table 20
[0407]
[0408] * "No" means no crystal transformation occurs and the original crystal form remains
[0409] 4: Comparative study of crystal habit
[0410] Weigh about 2 mg of each of the hydrochloride crystal form II sample prepared in Example 1 and the free base amorphous sample (prepared in Preparatory Example 2), place them on glass slides, add a small amount of vacuum silicone oil to disperse the samples, then cover them with coverslips and observe them under a polarizing microscope.
[0411] The experimental results show that the hydrochloride crystal form II is granular and has agglomeration ( Fig.67 ); amorphous is irregular particles ( Fig.68 ).
[0412] 5: Comparative study of grinding and pressure stability
[0413] Weigh about 10 to 30 mg of the hydrochloride salt form II sample prepared in Example 1 and the free base amorphous sample (prepared in Preparatory Example 2), respectively, and grind them manually with an agate mortar for about 10 minutes, and then test the sample XRPD; after being pressed into tablets at 350 MPa, the sample XRPD was tested.
[0414] The experimental results show that the hydrochloride crystal form II of the present invention does not change in crystal form after grinding or 350MPa pressure treatment, and the crystallinity of the sample changes only slightly ( Fig.69 After grinding, the amorphous dispersion peak further broadens; after tableting, the diffraction intensity of the dispersion peak increases ( Fig.70). Compared with the amorphous form, the hydrochloride crystal form II of the present invention has better grinding and pressure stability.
[0415] 6: Comparative study of wettability
[0416] Weigh about 200 mg of each of the hydrochloride crystal form II sample prepared in Example 1 and the free base amorphous sample (prepared in Preparatory Example 2), and after pressing each relevant solid form sample into a tablet, measure its contact angle to water.
[0417] The experimental results are shown in Table 21. Compared with the amorphous form, the experimental results show that the hydrochloride crystal form II of the present invention has a smaller contact angle and is more easily wetted by water.
[0418] Table 21
[0419] Material Contact Angle Hydrochloride Form II 72.4~76.7° Amorphous 80.0~83.3°
[0420] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile hydrochloride, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 5.2°±0.2°, 17.7°±0.2° and 10.4°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 13.2°±0.2°, 26.4°±0.2° and 19.9°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 22.4°±0.2°, 28.6°±0.2° and 26.0°±0.2°; Preferably, the crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 5.2°±0.2°, 17.7°±0.2°, 10.4°±0.2°, 13.2°±0.2°, 26.4°±0.2°, 19.9°±0.2°, 22.4°±0.2°, 28.6°±0.2° and 26.0°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in FIG1 .
2. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile hydrochloride, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 8.2°±0.2°, 9.9°±0.2° and 14.5°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 10.6°±0.2°, 11.0°±0.2°, 17.9°±0.2°, 19.1°±0.2°, 19.8°±0.2°, 20.3°±0.2°, 22.3°±0.2°, 25.3°±0.2° and 26.5°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in FIG5 .
3. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile hydrochloride, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 10.7°±0.2°, 17.2°±0.2° and 24.5°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 7.4°±0.2°, 12.6°±0.2°, 15.7°±0.2°, 16.7°±0.2°, 20.2°±0.2°, 21.1°±0.2°, 26.7°±0.2°, 27.2°±0.2°, 28.8°±0.2° and 30.7°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in FIG9 .
4. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile sulfate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 8.5±0.2°, 8.7°±0.2° and 12.5°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 15.7±0.2°, 16.9°±0.2° and 18.1°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in FIG13 .
5. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile sulfate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 3.4±0.2°, 14.8°±0.2° and 20.7°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 12.4±0.2°, 15.5°±0.2°, 16.9°±0.2°, 17.8°±0.2°, 20.4°±0.2°, 22.1°±0.2°, 24.9°±0.2°, 26.4°±0.2° and 27.8°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in FIG17 .
6. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile phosphate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 9.2±0.2°, 14.0°±0.2°, 17.0°±0.2° and 18.1°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at a diffraction angle 2θ of 3.1°±0.2°, 6.8°±0.2°, 7.5°±0.2°, 12.5°±0.2°, 15.1°±0.2°, 16.5°±0.2°, 17.6°±0.2°, 17.9°±0.2°, 18.7°±0.2°, 19.0°±0.2°, 20.3°±0.2° and 21.6°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in FIG. 21 .
7. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile fumarate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 7.2±0.2°, 41.7°±0.2°, and 14.3°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 13.5±0.2°, 22.3°±0.2°, 23.0°±0.2° and 25.3°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in FIG. 25 .
8. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile fumarate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 8.6±0.2°, 9.8°±0.2° and 14.3°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 7.2±0.2°, 11.7°±0.2°, 16.2°±0.2° and 26.9°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 29.
9. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile fumarate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 9.2±0.2° and 14.2°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 7.1±0.2°, 10.1°±0.2°, 21.8°±0.2°, 23.0°±0.2°, 24.3°±0.2°, 24.8°±0.2° and 27.4°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 33.
10. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile succinate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks at diffraction angles 2θ of 6.8±0.2° and 13.6°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 10.2±0.2°, 15.6°±0.2°, 17.5°±0.2° and 20.5°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 37.
11. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile methanesulfonate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 11.4±0.2°, 12.1°±0.2°, and 16.8°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 8.7±0.2°, 12.8°±0.2°, 18.2°±0.2° and 19.9°±0.2°. Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 41.
12. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile methanesulfonate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 11.4±0.2°, 12.1°±0.2°, and 16.8°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 14.3±0.2°, 15.6°±0.2°, 18.2°±0.2° and 26.1°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 45.
13. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile methanesulfonate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 8.8±0.2°, 15.3°±0.2°, 18.2°±0.2° and 21.5°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 6.1±0.2°, 9.7°±0.2°, 10.4°±0.2°, 11.9°±0.2°, 15.7°±0.2°, 17.5°±0.2°, 19.3°±0.2°, 20.9°±0.2°, 25.6°±0.2° and 26.7°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 49.
14. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile oxalate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 7.0±0.2°, 16.0°±0.2°, and 18.2°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 14.0±0.2°, 15.9°±0.2°, 16.7°±0.2°, 19.3°±0.2°, 20.1°±0.2° and 26.2°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 53.
15. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile ethanesulfonate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 11.4±0.2°, 17.9°±0.2°, and 19.1°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 5.7±0.2°, 7.1°±0.2°, 12.1°±0.2°, 14.2°±0.2° and 17.1°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 57.
16. A crystalline form of the compound 2-{3-[3-amino-4-(7H-pyrrolo[2,3-d]pyrimidin-4-yl)-1H-pyrazol-1-yl]-1-(isopropylsulfonyl)azetidin-3-yl}acetonitrile 2-hydroxyethanesulfonate, wherein: The crystalline form has an X-ray powder diffraction pattern including peaks located at diffraction angles 2θ of 11.4±0.2°, 17.7°±0.2°, and 19.1°±0.2°; Preferably, the X-ray powder diffraction pattern of the crystalline form further includes at least one peak located at diffraction angles 2θ of 5.7±0.2°, 12.2°±0.2°, 14.2°±0.2°, 15.3°±0.2°, 17.0°±0.2°, 20.9°±0.2°, 22.9°±0.2°, 22.4°±0.2° and 24.7°±0.2°; Preferably, the crystal form has an X-ray powder diffraction pattern as shown in Figure 57.
17. A pharmaceutical composition comprising the crystalline form of any one of claims 1 to 16.
18. Use of the crystalline form according to any one of claims 1 to 16 or the pharmaceutical composition according to claim 17 in preparing a medicament for treating a JAK kinase-mediated disease.
Citation Information
Patent Citations
Pyrrolopyrimidine derivative compound, pharmaceutical composition and application thereof
CN109867675A
Cited By
Application of JAK inhibitor to treatment of cerebral arterial thrombosis
CN122557558A